Background wage premia, beyond education: firm sorting and unobserved abilities - Luca Bonacini; Fabrizio Patriarca; Edoardo Santoni (Global Labor Organization (GLO), 2024)
This paper investigates the relationship between intergenerational inequality and differences in pay policies among firms. We examine whether the effects of parental background in firm selection contribute to the persistence of income inequality across generations, and particularly how this can enhance the understanding of transmission mechanisms beyond the traditional role of education. We first apply a two-way fixed-effects wage estimation, a' la AKM, to the Italian private sector. Our results indicate that the allocation of workers to firms with different wage policies is significantly influenced by the economic background of their parents. This influence on wages is significant and relatively greater than the impact of individual worker characteristics. Furthermore, the background effect amplifies from initial jobs to job changes and negatively affects the sorting between firm and worker types.
Keywords: I24; J21; J24; J31; 330; Firm effect; Intergenerational inequality; Labor market; Unobservable abilities; Wage inequality